Critical analysis of proximity-induced magnetism in MnTe / Bi2 Te3 heterostructures - Awana, G; Fujita, R; Frisk, A; Chen, P; Yao, Q; Caruana, AJ; Kinane, CJ; Steinke, N-J; Langridge, S; Olalde-Velasco, P; Dhesi, SS; van der Laan, G; et al. (American Physical Society, 2022)
An elegant approach to overcome the intrinsic limitations of magnetically doped topological insulators is to bring a topological insulator in direct contact with a magnetic material. The aspiration is to realize the quantum anomalous Hall effect at high temperatures where the symmetry-breaking magnetic field is provided by a proximity-induced magnetization at the interface. Hence, a detailed understanding of the interfacial magnetism in such heterostructures is crucial, yet its distinction from structural and magnetic background effects is a rather nontrivial task. Here, we combine several magnetic characterization techniques to investigate the magnetic ordering in MnTe/Bi2Te3 heterostructures. A magnetization profile of the layer stack is obtained using depth-sensitive polarized neutron reflectometry. The magnetic constituents are characterized in more detail using element-sensitive magnetic x-ray spectroscopy. Magnetotransport measurements provide additional information about the magnetic transitions. We find that the supposedly antiferromagnetic MnTe layer does not exhibit an x-ray magnetic linear dichroic signal, raising doubt that it is in its antiferromagnetic state. Instead, Mn seems to penetrate into the surface region of the Bi 2 Te 3 layer. Furthermore, the interface between MnTe and Bi 2 Te 3 is not abrupt, but extending over ∼ 2.2 nm. These conditions are the likely reason that we do not observe proximity-induced magnetization at the interface. Our findings illustrate the importance of not solely relying on one single technique as proof for proximity-induced magnetism at interfaces. We demonstrate that a holistic, multitechnique approach is essential to gain a more complete picture of the magnetic structure in which the interface is embedded.